The Victorian fairy tale book - Hearn, Michael Patrick (New York Pantheon Books, 1988)
A collection of classic Victorian fairy tales by such authors as John Ruskin, Charles Dickens, and Oscar Wilde.
Keywords: Fairy tales -- Great Britain; English fiction -- 19th century; Fairy tales; Short stories